Modulation of nutritional composition and aroma volatiles in cultivated pork fat by culture media supplementation - Sugama, Natsu; Lew, Emily T.; Riquelme-Guzmán, Camilo; Lee, Di Sheng; Li, Xinxin; Yuen, John S. K.; Lim, Taehwan; Kwan, Anson; Liu, Run Yi; Ma, Yoshene A.; Frost, Scott C.; Kaplan, David L. (Frontiers in Nutrition, 2025)
Cultivated meat is emerging as a novel food source with the potential to contribute to a more sustainable and ethical food production system. However, limited research to date has explored the extent to which the nutrition and the aroma of such foods can be altered through cell culture conditions. Here, we aimed to modulate the aromatic volatile compounds in heated porcine cultivated fat cells by manipulating the media components while ensuring the preservation of robust fat differentiation. Using dynamic headspace gas chromatography–mass spectrometry (DHS-GC–MS), we demonstrated that supplementing cells with thiamine-HCl increased its intracellular concentration and promoted the production of 4-methyl-5-thiazoleethanol, contributing to milky aroma. Similarly, supplementation with L-methionine enhanced its intracellular concentration and increased the production of methional, a volatile compound with a potato-like aroma. Additionally, myoglobin significantly altered the volatile organic compound profile of cultivated fat. Notably, the concentration of γ-nonalactone, (E, E)-2,4-decadienal and 2-pentylfuran were increased, which contribute to a coconut-like, deep fat, fruity aroma, respectively, as well as elevated levels of other alcohols, aldehydes and furans. These findings highlight the potential of culture media formulations to modulate the aroma in cultivated fat production, a unique opportunity to optimize sensory features using this novel food production technology.